Risk perception for Hepatitis B Virus (HBV) infection among health care workers in Accra,Ghana - Vivian Efua Senoo-Dogbey; Delali Adwoa Wuaku (Elsevier, 2022)
Background: Hepatitis B Virus (HBV) infection is recognized as one of the most important occupational hazards to Health Care Workers (HCWs) globally. HCWs having good risk perception, is critical in adopting and adhering to preventive measures against occupational exposures and subsequent infection with the virus. This study assessed the level of risk perception for HBV infection among healthcare workers in five healthcare settings in Accra, Ghana, and identified how risk perception for HBV varies across the various professional categories. Method: A cross-sectional study was conducted among six cadres of healthcare workers from five facilities in 2019. A structured questionnaire and susceptibility sub-scale was adapted and used to collect data. Data were analyzed using SPSS Software version 25. Results: There were 313 HCWs who participated in the study. Mean age, 35 years (±7.6). The overall mean risk perception score was 92.3. There was a significant difference in risk perception scores between the six cadres of staff (F = 3.26, df 312, p = 0.007). A Post Hoc analysis showed a significant difference between the risk perception scores of Doctors and Orderlies, mean difference of 6.723, (p = 0.017; 95% CI = 0.83-12.60). Post-tertiary level education and training in infection prevention and control were significantly associated with high-risk perception for HBV. Conclusion: HCWs have a high-risk perception for HBV infection and the risk perception varies across the various professional categories. The high level of risk perception observed in this study could be utilized to design preventive interventions for healthcare workers to prevent occupational exposures and subsequent infections.